Enhancing socially shared regulation in collaborative learning groups: designing for CSCL regulation tools - Järvelä, Sanna; Kirschner, Paul A.; Panadero, Ernesto; Malmberg, Jonna; Phielix, Chris; Jaspers, Jos; Koivuniemi, Marika; Järvenoja, Hanna (Educational technology research and development, 2015)
For effective computer supported collaborative learning (CSCL), socially shared regulation of learning (SSRL) is necessary. To this end, this article extends the idea first posited by Järvelä and Hadwin (Educ Psychol 48(1):25–39, 2013) that successful collaboration in CSCL contexts requires targeted support for promoting individual self-regulatory skills and strategies, peer support, facilitation of self-regulatory competence within the group, and SSRL. These (meta)cognitive, social, motivational, and emotional aspects related to being/becoming aware of how one learns alone and with others are for the most part neglected in traditional CSCL support. Based upon a review of theoretical and empirical studies on the potential of and challenges to collaboration, three design principles for supporting SSRL are introduced: (1) increasing learner awareness of their own and others' learning processes, (2) supporting externalization of one's own and others' learning process and helping to share and interact, and (3) prompting acquisition and activation of regulatory processes. Finally, an illustrative example is presented for how these principles are applied in a technological tool for supporting SSRL.